Character Formation in The First 1000 Days in Qs. Al-Mu’minun and Qs. Maryam - Okti Nurvadila; Selvia Rahma Sari; Nasywa Intan Azzahra (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
This research explores the critical role of character development within the First 1000 Days of Life (F1000DoL) through the lens of the Qur'an, specifically examining Surah Al-Mu'minun, Maryam, Ibrahim, Al-Ahzab, and Al-A'raf. The F1000DoL, spanning from conception to a child's second birthday, is recognized as a crucial period influencing physical, cognitive, emotional, and moral growth. Employing a qualitative approach with literature review and content analysis, this study reveals a convergence between medical science and Qur'anic teachings on the significance of early life stages for character formation. The Qur'an highlights the impact of a mother's emotional and spiritual state during pregnancy. Character education strategies include nurturing affection, providing positive role models, instilling religious values through habit, and offering parental prayers. This study aims to offer a deeper understanding of how Qur'anic principles can optimize early childhood character development.